Community acquired bacteraemia in the elderly - Whitelaw, D A; Whitelaw, D A (Department of Medicine, 2017)
Age affects the human frame at all levels - from the skin which is ravaged by exposure to ultraviolet light and toxic irritants to the immune system which becomes progressively less responsive to antigenic stimuli. Bacteraemia follows a focal infection and thus any change which results in increased infection will result in an increased chance of bacteraemia. Therefore any factors bearing on focal infection will, of necessity influence not only the possibility but also the severity of a bacteraemia.